2011
DOI: 10.1371/journal.pone.0014496
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Changes and Word Finding Failures with Increasing Age

Abstract: BackgroundIncreasing life expectancy necessitates the better understanding of the neurophysiological underpinnings of age-related cognitive changes. The majority of research examining structural-cognitive relationships in aging focuses on the role of age-related changes to grey matter integrity. In the current study, we examined the relationship between age-related changes in white matter and language production. More specifically, we concentrated on word-finding failures, which increase with age.Methodology/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 56 publications
9
53
1
Order By: Relevance
“…We have previously shown that increased RIFG activation is related to preserved performance in participants more prone to making errors and may play a role in counteracting competing inputs (Stamatakis et al. 2011; Geva et al. 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that increased RIFG activation is related to preserved performance in participants more prone to making errors and may play a role in counteracting competing inputs (Stamatakis et al. 2011; Geva et al. 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2008; Stamatakis et al. 2011; Antonenko and Flöel 2014; Geerligs et al. 2014) and segregation of functional networks with age (Oldfield 1971; Chan et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have linked lower language performance in older adults to deterioration in bilateral white matter microstructure, as measured by fractional anisotropy (FA) using magnetic resonance imaging (MRI)-based diffusion tensor imaging (DTI; Obler et al, 2010;Stamatakis et al, 2011). For example, Obler et al (2010) found that naming performance was correlated to FA values in left-hemisphere language-relevant brain regions as well as their right-hemisphere homologues.…”
Section: Introductionmentioning
confidence: 99%